2020
DOI: 10.1007/s13205-020-02230-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and anticancer efficacy of novel cobalt oxide nanoparticles conjugated with thiosemicarbazide

Abstract: Gastric cancer is one of the most common cancers in modern societies. Previous studies have shown that the use of nanoparticle complexes is effective in the treatment of cancer. The aim of this study was to investigate the cytotoxicity and anticancer properties of cobalt oxide (Co 3 O 4 ) nanoparticles (NPs) functionalized by glutamic acid (Glu) and conjugated with thiosemicarbazide (TSC) on gastric cancer (AGS) cell line. First, the Co 3 O 4 @Glu/TSC nanoparticles were synthesized via co-condensation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Our recent work also demonstrated that cobalt oxide nanoparticles showed high toxicity against cancer cells while the same concentrations would not induce cytotoxicity against normal cells [20]. Moreover, cobalt oxide nanoparticles were also found to exert anticancer effects by inducing apoptosis or causing DNA damage [21,22]. Last but not least, cobalt oxide nanoparticles could also act as delivery systems with drugs or antigens encapsulated for targeted cancer therapy, causing more selective cancer cell death or stimulating selective anticancer immune responses [23][24][25].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our recent work also demonstrated that cobalt oxide nanoparticles showed high toxicity against cancer cells while the same concentrations would not induce cytotoxicity against normal cells [20]. Moreover, cobalt oxide nanoparticles were also found to exert anticancer effects by inducing apoptosis or causing DNA damage [21,22]. Last but not least, cobalt oxide nanoparticles could also act as delivery systems with drugs or antigens encapsulated for targeted cancer therapy, causing more selective cancer cell death or stimulating selective anticancer immune responses [23][24][25].…”
Section: Introductionmentioning
confidence: 92%
“…Jarestan. M. et al obtained Co 3 O 4 @Glu/TSC NPs by contraction and investigated their cytotoxicity on gastric cancer cells [21]. The obtained nanocomplex is coated with glutamic acid to show better moisture properties.…”
Section: Selective Cancer Cell Inhibition By Cobalt Oxide Nanoparticlesmentioning
confidence: 99%
“…There are reports that suggest that treatment with nickel nanoparticles can induce anticancer activities in different types of cancer cells [13][14][15][16]. Cobalt nanoparticles also possess anti-cancer activities, as shown in several studies [17][18][19][20]. Besides, gallium nanoparticles also show anti-cancer drug delivery and cancer cell imaging capabilities [21][22][23].…”
Section: Introductionmentioning
confidence: 94%
“…Potentially ditopic Schiff bases prepared from oxamic or thioxamic hydrazide have been widely reported in the literature by chemists and in particular those interested in coordination chemistry [1][2][3][4][5][6]. Oxamic hydrazide has two different arms.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of heterocyclic molecules with good medicinal properties are obtained starting from these oxamic precursors [18]. They are used as antibacterial agent, [19] anticonvulsant, [8] antiinflammatory [20], antituberculosis [18] and anticancer agents [4,21]. Schiff's bases are synthesized from oxamic hydrazide and used for the preparation of complexes with transition metal and lanthanide ions [9,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%